Securing the base of the appendix during laparoscopic appendectomy - Samir Delibegović; Reuf Karabeg; Milan Simatović (Medicinski glasnik, 2020)
In contrast to classical appendectomy where the appendiceal stump is secured by a single or double ligature, in laparoscopic appendectomy various ways of securing the stump are mentioned. Each of these methods has advantages and disadvantages. Since different possibilities exist for closing the stump, it is very important to find the optimum method for closure of the appendiceal stump, bearing in mind their simplicity, biocompatibility and price. The aim of this review article has been to present the problem of securing the base of the appendix during laparoscopic appendectomy.
Keywords: appendix; laparoscopic appendectomy; linear stapler; titanium